Research on Ship Exhaust Gas Accounting in Yangtze River. Issue 4 (February 2020) - Gao, Zheng; Zhou, Yi; Wang, Mingdong
Abstract: Based on the comparison and analysis of existing ship exhaust emission accounting methods, and combined with the characteristics of ship exhaust emissions in the Yangtze River channel, this paper selects the appropriate calculation idea, and revises the basic accounting method of ship exhaust emissions according to the calculation accuracy requirements in this paper. Finally, a calculation model for the emissions of ships in the Yangtze River channel is established, and its reliability and accuracy have been confirmed by model tests of the model data. In this paper, the Yangtze River ships are divided into sea-going ships and inland river ships, and their corresponding parameters are calculated respectively, in order to make sure that the accounting results have higher accuracy. The model has strong applicability to the exhaust emission of ships in the Yangtze River, and its calculation results are relatively accurate, and the calculation process is simple and efficient. This paper has a very high social significance and practical value for the analysis and model optimization study of the Yangtze River's exhaust emission accounting.